Proactive notification system using instant messaging bot (IM bot) - Abdul Aziz S.R.; Razalan A.A.-F.; Noor N.M.; Sauti M.S. (2023)
Instant messaging (IM) is a real-time communication system providing people with medium to exchange text messages, images, audio and video conversation. Using the same concept, IM is exploited and used for system administration purpose. This paper briefly describes the functionality provided by a developed IM bot that provide system administrator with remote machine status and information. The tool proactively detects the machine presence on the IM network thus allowing system administrator to interact with them. With the real-time nature of IM, this tool would benefit system administrator with real-time system status and notification messages. In addition, the machine list within IM provides system administrator with the inventory of the machines currently being maintained. The output comparison between the program's plugin and the result from the system as shown through Linux terminal are provided which includes the information of system load average, system memory usage, logged-in user and notification service. 2010 IEEE.